Leveraging Blockchain Technology for Sustainable Economic Development in Vietnam: Applications and Implications in the Context of the 4.0 Industrial Revolution - Huyen, Le Thi Thu; Lan, Le Thi; Nhung, Ong Thi (International Journal of Scientific Research and Management (IJSRM), 2024)
This study was conducted to explore the potential of blockchain technology in sustainable economic development in Vietnam. Using qualitative research methods, based on the study of relevant literature, the study highlights the various applications of blockchain in areas such as supply chain management, inclusive finance, energy management and asset rights. The study also emphasizes the importance of addressing challenges for successful adoption of blockchain technology. It identifies the need for a supportive regulatory framework that clarifies legal and regulatory aspects related to blockchain, ensuring its legality and promoting innovation. Furthermore, the study highlights the importance of investing in the necessary technical infrastructure and ensuring interoperability among different blockchain platforms. Skill development is also crucial, as there is a need for a qualified workforce capable of developing and implementing blockchain solutions. By leveraging blockchain technology and addressing these challenges, Vietnam can achieve sustainable economic development. The study concludes that embracing blockchain technology can position Vietnam as a leader in the 4.0 industrial revolution, fostering innovation, transparency, and efficiency across sectors and contributing to the country's overall economic growth and development.